Distúrbios hemostáticos e atividade das enzimas que hidrolisam nucleotídeos e nucleosídeo de adenina em cães infectados com Rangelia vitalii - Paim, Carlos Breno Viana (2012)
The parasite Rangelia vitalii is the etiologic agent of rangeliosis, a disease that leads to a wide variety of clinical signs, including hemostatic disorders characterized by bleeding. However, the causes of this process have not been established. The aim of this study was to evaluate the production of megakaryocytes, platelet count, clotting time, platelet activity and to determine the activity of enzymes that hydrolyze nucleotides and adenine nucleosides in platelets of dogs experimentally infected with R. vitalii. For this study, 12 dogs were separated in two groups: Group A was composed by five healthy dogs, and group B composed by seven dogs experimentally infected with R. vitalii. After inoculation, the animals were monitored by blood smears. The parasite was found within erythrocytes, neutrophils and monocytes five days post-inoculation (PI). Blood collection to perform platelet count, coagulation tests and measurement of platelet aggregation was performed on days 0, 10 and 20 PI. On days 10 and 20 PI, after this procedure, the dogs were anesthetized for collecting bone marrow samples to evaluate the production of megakaryocytes. To measure the activity of ectonucleotidases and adenosine deaminase, blood samples were collected on days 12 and 21 PI. Blood samples were stored in tubes containing EDTA to quantification of platelets, evaluation of platelet aggregation and measurement of enzymatic activity. The blood was stored in tubes containing citrate for realization of the clotting time. This study revealed a reduction (P<0.01) of platelet numbers in the infected group when compared to control group. Prothrombin time and active partial thromboplastin time showed no significant difference between infected and control animals. There was an increase (P<0.01) in the number of megakaryocytes in infected group when compared with control group. A reduction (P<0.01) of platelet aggregation was observed in dogs infected with R. vitalii. The hydrolysis of ATP, ADP, AMP and deamination of adenosine decreased (P<0.01) on day 12 PI. On day 21 PI, the activity of adenosine deaminase remained reduced (P<0.01), whereas it was observed an increase (P<0.05) in NTPDase levels. From these results, we can conclude that rangeliosis is responsible for severe thrombocytopenia during the acute phase of infection, and this can be due to splenic sequestration and/or immune-mediated thrombocytopenia. Also, alterations in purinergic system contribute to the occurrence of hemostatic disorders observed in this disease.